Ten years follow‐up retrospective study on implant survival rates and prevalence of peri‐implantitis in implant‐supported full‐arch rehabilitations. Issue 3 (18th February 2019) - Francetti, Luca; Cavalli, Nicolò; Taschieri, Silvio; Corbella, Stefano
Abstract: Objectives: The aim of the present paper was to present medium‐ and long‐term data on implant survival and on the prevalence of peri‐implantitis in a cohort of patients treated with full‐arch rehabilitations. Materials and methods: Clinical records of all patients treated with immediately loaded full‐arch rehabilitation in the Dental Clinic of the IRCCS Istituto Ortopedico Galeazzi in Milan, Italy, supported by moderately rough implants were retrospectively examined to calculate survival curves for implant loss and for the occurrence of peri‐implantitis (both at implant‐ and at patient level). Regression methods were used to evaluate the correlation between the presence of periodontitis and smoking habits with the outcomes. Results: A total of 384 implants placed in 77 patients (96 rehabilitations) were evaluated for a mean period of 8.0 years (range 1.0–13.7 years) from loading. After 10 years, the cumulative survival rate was 96.11% (95% CI: 99.17%–93.05%; 84 implants) while the cumulative rate of implants free from peri‐implantitis was 86.92% (95% CI: 82.14%, 91.71%; 60.69% [95% CI: 44.19%, 77.19%] at patient level). The cumulative proportion of implants without peri‐implantitis after 10 years was significantly higher in mandible (89.76%, 95% CI: 84.49%, 95.03%) than in maxilla (81.71%, 95% CI: 71.91%, 91.51%; p  = 0.028). No correlation was found between periodontal and smoking status and outcomes. Conclusions: The study reported high 10‐year implant survival rate for full‐arch rehabilitations since implant loss was relatively rare. Peri‐implantitis was relatively frequent in the examined population although the number of subjects available for 10‐year evaluation was limited.